Towards a geography of voice-hearing. (August 2021) - Nieuwenhuis, Marijn; Knoll, Emily
Abstract: The social psychiatrists Marius Romme and Sandra Escher argue that boundaries are of critical importance in the therapeutic treatment of so-called 'auditory verbal hallucinations' (AVH), or, what is better known as, 'hearing voices'. Limiting voices to a specific time and place, they argue, helps 'voice-hearers' to take back control from their voices. This paper draws inspiration from contemporary debates on sonic geographies to explore what it means for voice-hearers to engage in a complex relationship with their voices. We analyse a range of material and affective spaces to understand what it means for a voice-hearer to transcend, mediate and rework the boundaries between interior and exterior worlds. Besides a detailed conceptual discussion on the geography of voices and voicehearing, we conducted semi-structured interviews with a sample of thirty voice-hearers in North-East and South-East England to gain insight into their voice geographies. The participants move us to appreciate how voice-hearers construe relationships with their voices in complex and ambiguous ways. Some voice-hearers were able to challenge and even change the balance of power, allowing them to be 'in control', while others were not. The paper is aimed at introducing voice-hearing to a growing body of work on geographies of the voice. Highlights: A geography of voice hearing. An conceptual critique of existing geographic and embodied approaches to the voice. A discussion on the negotiation of the spaces that a voice inhabits.